Analysis of diamondoids on metallic surfaces with scanning probe Microscopy - Stiefermann, Marvin; Justus Liebig University Giessen (My University, 2017)
In this work, we based the determination of self-assembled monolayers on Scanning Probe Microscopy (SPM). We focused on two different aspects of SPM. The frst aspect concerns the instrumentation applied in this research. With the development of new techniques and their ongoing application and improvement, all parameters needed for the exact deduction of results inevitably have to be determined. We carried out measurements and simulations which helped to clarify the spring constant for the common qPlus sensor. This sensor is the new standard tool for high-precision scanning probe techniques. The second focus in this work is the structure of self-assembled monolayers. With the application of high resolution, submolecular scanning probe techniques, we studied the island structure of two diamondoids (namely [121]Tetramantane] and [123]Tetramantane), as well as their exact orientations, with a never before seen distinction between similar molecules.
Keywords: ddc:530